Big Things - Little Things - D D Pretzer (Kansas Agricultural Experiment Station Research Reports, 1982)
This study examined the economic effects of applying controllable management factors for farrow-to-finish operations. Average producers in Kansas market 7 pigs/litter with an average feed conversion of 4.58. Improvement in 9 areas of management increased profits on 240 litters by 43,680. Each item appears small. However "Big Things" come from the sum of "Little Things".; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Management factors; Farrow-to-finish operations